Zaï and the half-moon - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Two techniques zaï (an ancestral method of the Mossi in Burkina Faso, mentioned in Spore 87, page 15) and half-moon (which is very current in Cape Verde) are well-known measures against soil degradation in arid and semi-arid zones. The...